Nutritional management and postoperative prognosis of newborns submitted to primary surgical repair of gastroschisis - Flavia Miranda da Silva Alves; Marcelo Eller Miranda; Marcos José Burle de Aguiar; Maria Cândida Ferrarez Bouzada Viana (Elsevier, 2016)
Objective: Gastroschisis is a defect of the abdominal wall, resulting in congenital evisceration and requiring neonatal intensive care, early surgical correction, and parenteral nutrition. This study evaluated newborns with gastroschisis, seeking to associate nutritional characteristics with time of hospital stay. Methods: This was a retrospective cohort study of 49 newborns undergoing primary repair of gastroschisis between January 1995 and December 2010. The newborns' characteristics were described with emphasis on nutritional aspects, correlating them with length of hospital stay. Results: The characteristics that influenced length of hospital stay were: (1) newborn small for gestational age (SGA); (2) use of antibiotics; (3) day of life when enteral feeding was started; (4) day of life when full diet was reached. SGA infants had longer length of hospital stay (24.2%) than other newborns. The length of hospital stay was increased by 2.1% for each additional day taken to introduce enteral feeding. However, slower onset of full enteral feeding acted as a protective factor, decreasing length of stay by 3.6%. The volume of waste drained by the stomach catheter in the 24 h prior the start of enteral feeding was not associated with the timing of diet introduction or length of hospital stay. Conclusion: Early start of enteral feeding and small, gradual increase of volume can shorten the use of parenteral nutrition. This management strategy contributes to reduce the incidence of infection and length of hospital stay of newborns with gastroschisis. Resumo: Objetivo: a gastrosquise é uma malformação da parede abdominal que resulta em evisceração congênita, e requer tratamento intensivo neonatal, correção cirúrgica precoce e nutrição parenteral. Investigou-se neste estudo os recém-nascidos com gastrosquise, procurando correlacionar as suas características nutricionais com o tempo da internação hospitalar. Métodos: estudo de coorte retrospectivo de 49 recém-nascidos submetidos à correção primária de gastrosquise no período de janeiro de 1995 a dezembro de 2010. As características dos neonatos foram descritas com ênfase nos aspectos nutricionais relacionando-as com o tempo de internação hospitalar. Resultados: as características que influenciaram a duração da internação foram: 1) recém-nascidos pequenos para a idade gestacional (PIG); 2) uso de antibióticos; 3) dia de vida ao iniciar a dieta enteral; 4) dia de vida ao atingir a dieta plena. Recém-nascidos PIG tiveram maior tempo de internação (24,2%) que demais neonatos. O tempo de internação foi aumentado em 2,1% para cada dia a mais que se demorou a introduzir a dieta enteral. Entretanto, atingir mais lentamente o aporte pleno da dieta enteral agiu como fator protetor, diminuindo 3,6% no tempo de internação. O volume de resíduo drenado pelo cateter gástrico, nas últimas 24 horas antes do início da dieta enteral, não apresentou correlação com o momento da introdução da dieta, nem com a duração da hospitalização. Conclusão: iniciar a dieta enteral precocemente, com aumento gradativo em pequenos volumes pode abreviar a duração da nutrição parenteral. Este manejo contribui para a diminuição da incidência de infecções e do tempo de hospitalização de recém-nascidos com gastrosquise. Keywords: Gastroschisis, Nutrition, Length of hospital stay, Palavras-chave: Gastrosquise, Nutrição, Tempo de hospitalização